Desenvolvimento de resina novolac derivada do líquido da casca da castanha de caju para aplicação em revestimentos anticorrosivos - Marciano, Sara Jéssica (2023)
Brazil stands out globally in the production of cashew nuts, and one of the main byproducts generated in the cashew nut processing industry is Cashew Nut Shell Liquid (CNSL). CNSL is a natural, renewable, and abundant source rich in phenolic compounds, obtained as a byproduct of the cashew agribusiness, with low added value. Thus, this study aimed to find a purpose for CNSL and add value to it through the synthesis of entirely biobased novolac resins for coating production, acting in copolymer formation by blending with the commercial resin bisphenol A diglycidyl ether (DGEBA). The reaction procedure was conducted using CNSL and furfural to obtain novolac-type resins, whose chemical structures were characterized by Fourier Transform Infrared Spectroscopy (FT-IR) and 1H Nuclear Magnetic Resonance Spectroscopy (1H NMR). The thermal stability of the polymers was assessed through Thermogravimetric Analysis, and the resin polymerization study was investigated by Differential Scanning Calorimetry (DSC). The TGA thermogram results demonstrate excellent thermal stability with values under N2 atmosphere in the range of 400 °C. Coatings were produced from CNSL- Fu/DGEBA resin formulations in different ratios using 1-methylimidazole as a catalyst and exhibited satisfactory anticorrosive properties analyzed by Electrochemical Impedance Spectroscopy (EIS), influenced by increased material cross-linking degree. The results indicated satisfactory impedance modulus values at low frequencies, showing that the coatings acted as a barrier, effectively promoting metal protection.